Revealing the vertical structure of in-situ fabricated perovskite nanocrystals films toward efficient pure red light-emitting diodes - Wu, Xian-gang; Sun, Shipei; Song, Tinglu; Zhang, Xin; Wang, Chenhui; Yang, Yingguo; Wang, Shuangpeng; Zhong, Haizheng (Fundamental research (Beijing), 2024)
The development of efficient perovskite light-emitting diodes (PeLEDs) relies strongly on the fabrication of perovskite films with rationally designed structures (grain size, composition, surface, etc.). Therefore, an understanding of structure-performance relationships is of vital importance for developing high-performance perovskite devices, particularly for devices with in-situ fabricated perovskite nanocrystal films. In this study, we reveal the vertical structure of an in-situ fabricated quasi-two-dimensional perovskite film. By combining time-of-flight secondary ion mass spectrometry, energy dispersive spectroscopy, grazing incidence wide-angle X-ray scattering (GIWAXS), and low-temperature photoluminescence spectra, we illustrate that the resulting in-situ fabricated DPPA2Csn-1Pbn(Br0.3I0.7)3n+1 (DPPA+: 3,3-diphenylpropylammonium) film has a gradient structure with a very thin layer of ligands on the surface, predominantly small-n domains at the top, and predominantly large-n domains at the bottom owing to the solubility difference of the precursors. In addition, GIWAXS measurements show that the domain of n = 2 on the top layer has an ordered in-plane alignment. Based on the understanding of the film structure, we developed an in-situ fabrication process with ligand exchange to achieve efficient pure red PeLEDs at 638 nm with an average external quantum efficiency (EQE) of 7.4%. The optimized device had a maximum luminance of 623 cd/m2 with a peak EQE of 9.7%. [Display omitted]